ISWI is a RanGTP-dependent MAP required for chromosome segregation - Yokoyama, Hideki (The Rockefeller University Press, 2009)
Production of RanGTP around chromosomes induces spindle assembly by activating nuclear localization signal (NLS)–containing factors. Here, we show that the NLS protein ISWI, a known chromatin-remodeling ATPase, is a RanGTP-dependent microtubule (MT)-associated protein. Recombinant ISWI induces MT nucleation, stabilization, and bundling in vitro. In Xenopus culture cells and egg extract, ISWI localizes within the nucleus in interphase and on spindles during mitosis. Depletion of ISWI in egg extracts does not affect spindle assembly, but in anaphase spindle MTs disappear and chromosomes do not segregate. We show directly that ISWI is required for the RanGTP-dependent stabilization of MTs during anaphase independently of its effect on chromosomes. ISWI depletion in Drosophila S2 cells induces defects in spindle MTs and chromosome segregation in anaphase, and the cells eventually stop growing. Our results demonstrate that distinctly from its role in spindle assembly, RanGTP maintains spindle MTs in anaphase through the local activation of ISWI and that this is essential for proper chromosome segregation.